Microfluidics and cancer analysis: cell separation, cell/tissue culture, cell mechanics, and integrated analysis systems. Issue 2 (18th November 2015) - Pappas, Dimitri
Abstract : Among the growing number of tools available for cancer studies, microfluidic systems have emerged as a promising analytical tool to elucidate cancer cell and tumor function. Abstract : Among the growing number of tools available for cancer studies, microfluidic systems have emerged as a promising analytical tool to elucidate cancer cell and tumor function. Microfluidic methods to culture cells have created approaches to provide a range of environments from single-cell analysis to complex three-dimensional devices. In this review we discuss recent advances in tumor cell culture, cancer cell analysis, and advanced studies enabled by microfluidic systems.